The Relationship between Capital Market and Economic Growth in Thailand - Wanaset, Apinya (Journal of Applied Economics and Management Strategy, 2018)
The aims of this study were twofold: 1) to overview the capital market and economic growth in Thailand; and 2) to examine the relationship between economic growth and the capital market, including the stock market and bond market after the financial crisis in 1997. Both descriptive and quantitative analyses were employed in this study. The descriptive analysis explained the structure and development of the capital market in Thailand. A cointegration and causality test were employed for the quantitative analysis in order to investigate the long-term relationship and pairwise relationship between the variables. The variables used in this study were time series data, including gross domestic product (GDP), market capitalization in the Stock Exchange of Thailand, and the outstanding debt instrument in the bond market for the period 1997-Q1 through 2016-Q4. The results of the study showed that, one, during the past two decades, both the stock market and bond market in Thailand tended to have greater development, especially with the bond market growing more than 20 times. Regarding the stock market, it collapsed in the 1997 financial crisis in Thailand, and after that crisis, it slowly recovered. At present, the stock market is over 5 times larger than the bond market. The second result from the study indicated that economic growth had positive impacts on both the stock market and bond market. As the Thai economy has expanded, private companies and households have received higher incomes and have become wealthier, thus promoting savings and investment through the capital markets. At the same time, the stock market has also supported economic growth by funding allocation to private investment, leading to the enlargement of the manufacturing sector and employment. However, the bond market was not seen to have a significant effect on the economic growth in Thailand during this period of time. Keywords: Capital Market, Economic Growth, Cointegration, Causality